2009
DOI: 10.1021/nl9004833
|View full text |Cite
|
Sign up to set email alerts
|

Soft Graphoepitaxy of Block Copolymer Assembly with Disposable Photoresist Confinement

Abstract: We demonstrate soft graphoepitaxy of block copolymer assembly as a facile, scalable nanolithography for highly ordered sub-30-nm scale features. Various morphologies of hierarchical block copolymer assembly were achieved by means of disposable topographic confinement of photoresist pattern. Unlike usual graphoepitaxy, soft graphoepitaxy generates the functional nanostructures of metal and semiconductor nanowire arrays without any trace of structure-directing topographic pattern. Our novel approach is potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 43 publications
2
121
0
Order By: Relevance
“…Aligning symmetric PS-b-PMMA (lamellae) has proven much more difficult when substrate topography is introduced as the PMMA components tend to wet the SiO x mesa sidewall and trench base interfaces. To this end, researchers have devised elaborate schemes for balancing the interfacial energies by using gold strips evaporated onto PS-r-PMMA brush layers [99] or the actual resist pattern for mesa structures [113]; using the alignment properties of a commensurate asymmetric PS-b-PMMA system to create a chemical pre-pattern for directing the lamellae structure [112] or evaporating amorphous silicon onto a PS-r-PMMA combined with tapered trench designs for local defect density minimisation [114]. Figure 10(b) shows a schematic top down and cross sectional lay-out of the tapered substrate approach used to limit defect formation within the channel.…”
Section: Graphoepitaxymentioning
confidence: 99%
See 2 more Smart Citations
“…Aligning symmetric PS-b-PMMA (lamellae) has proven much more difficult when substrate topography is introduced as the PMMA components tend to wet the SiO x mesa sidewall and trench base interfaces. To this end, researchers have devised elaborate schemes for balancing the interfacial energies by using gold strips evaporated onto PS-r-PMMA brush layers [99] or the actual resist pattern for mesa structures [113]; using the alignment properties of a commensurate asymmetric PS-b-PMMA system to create a chemical pre-pattern for directing the lamellae structure [112] or evaporating amorphous silicon onto a PS-r-PMMA combined with tapered trench designs for local defect density minimisation [114]. Figure 10(b) shows a schematic top down and cross sectional lay-out of the tapered substrate approach used to limit defect formation within the channel.…”
Section: Graphoepitaxymentioning
confidence: 99%
“…Li et al have shown that PS-b-PMMA can be directed into linear arrays of parallel PMMA cylinders or hexagonal packed vertically cylinders by subtle film thickness changes using nano-imprinting on a random copolymer brush [94] Graphoepitaxy is undoubtedly a valuable and effective resolution enhancement technique for creating sub 10 nm nanoscale devices. Although graphoepitaxy is a viable approach to realising nanoscale devices, certain challenges must be overcome for the technique to be accepted for future 'complimentary' lithographic technologies, such as channel width and confinement [26,99,110,112,122], mesa to trench dimension [98,122], effect of trench wall and base chemistry [112][113]123] and importantly inhibit defect formation within both the top-down template pattern and bottom-up polymer self-assembled nanopattern [114].…”
Section: Graphoepitaxymentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of periodic nanoscale morphologies such as sphere or cylinder array, or lamellae self-assembled in block copolymer thin films enable ultrafine and dense nanopatterning with the characteristic dimension of a 5$50 nm scale. [19][20][21][22][23][24][25][26][27][28] The scalable and parallel assembly of block copolymers enables large-scale nanopatterning with fine tunability over the shape, density, and characteristic dimensions. Despite its enormous advantages, block copolymer lithography has thus far mostly been employed for the fabrication of electronic or magnetic nanostructures.…”
Section: 14mentioning
confidence: 99%
“…The directed self-assembly (DSA) of BCP thin films using chemical [3][4][5][6][7][8] or topographical [9][10][11][12][13][14][15][16] templates to impose long-range order and registration on the BCP domains has garnered increased interest in recent years as a means to enhance lithographic resolution by multiplying the feature density [5][6][7][8][13][14][15] and rectifying pattern non-uniformity or imperfections 5,6,17,18 of lithographically defined templates. Selective removal or alteration of one block then creates a mask that may be combined with other manufacturing techniques to fabricate devices such as patterned magnetic recording media 19 , silicon nanowire transistors 20 or FinFETs 21 .…”
mentioning
confidence: 99%